2002
DOI: 10.1210/mend.16.7.0863
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Induction of NUR77/NURR1 in Corticotrophs by CRH/cAMP: Involvement of Calcium, Protein Kinase A, and MAPK Pathways

Abstract: Nur factors are critical for proopiomelanocortin (POMC) induction by CRH in corticotrophs, but the pathways linking CRH to Nur are unknown. In this study we show that in AtT-20 corticotrophs CRH and cAMP induce Nur77 and Nurr1 expression and transcription at the NurRE site by protein kinase A (PKA) and calcium-dependent and -independent mechanisms. Calcium pathways depend on calmodulin kinase II (CAMKII) activity, and calcium-independent pathways are accounted for in part by MAPK activation (Rap1/B-Raf/MAPK-ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
78
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(88 citation statements)
references
References 52 publications
7
78
1
2
Order By: Relevance
“…For the NR4A subfamily, the AF1 appears to play the predominant role in transcriptional activation and co-factor recruitment, and its activity can be regulated by phosphorylation (21)(22)(23)(24)(25)(26). Recent results show that the AF1 directly recruits co-activators such as members of the SRC family, p300, pCAF, and DRIP205 (25,26).…”
mentioning
confidence: 99%
“…For the NR4A subfamily, the AF1 appears to play the predominant role in transcriptional activation and co-factor recruitment, and its activity can be regulated by phosphorylation (21)(22)(23)(24)(25)(26). Recent results show that the AF1 directly recruits co-activators such as members of the SRC family, p300, pCAF, and DRIP205 (25,26).…”
mentioning
confidence: 99%
“…By 4 h, the relative mRNA levels for Nur77 and [7-12, 20, 21], there has been increased interest in regulation of their expression by various inflammatory stimuli, including LPS [10]. Several studies have shown that NR4A expression can be induced by cAMP [13][14][15][16]19], whose intracellular levels can be increased in response to mediators of inflammation or stress such as prostaglandins or catecholamines. However, potential interactions between LPS and cAMP analogs or cAMP-elevating agents in regulating NR4A expression have not been reported previously.…”
Section: Simultaneous Treatment With 8-bromo-camp Clearly Modified Thmentioning
confidence: 99%
“…The present results indicate that the regulated expression of NR4A members within macrophages in vivo and the resulting functional consequences are likely to be significantly more complex than appreciated from previous studies that evaluated regulation of NR4A expression by single stimuli in cultured cells. In addition to inducing NR4A expression, the cAMP/protein kinase A pathway can enhance transcriptional activity of NR4A receptors independently of changes in NR4A levels [14,22], thus potentially adding yet another layer of regulatory complexity. …”
Section: Simultaneous Treatment With 8-bromo-camp Clearly Modified Thmentioning
confidence: 99%
See 1 more Smart Citation
“…At the pituitary level, CRH stimulates the expression of pro-opiomelanocortin (Pomc) and production of adrenocorticotropin (ACTH) (Gagner & turn activate the Pomc promoter. cAMP activates calcium/ calmodulin kinase II and Rap1/B-raf/ERK1/2 (Kovalovsky et al 2002) to induce expression of Nur77/ Nurr1 (Murphy & Conneely 1997, Philips et al 1997, Maira et al 1999, which then triggers transcription of Pomc via the NurRE consensus site in the promoter of Pomc. CRH also induces the transcriptional activity of activating protein 1 (AP1) and CREB, which promotes transcription of Pomc through the AP1-binding site located in the first exon (Boutillier et al 1995(Boutillier et al , 1998.…”
Section: Introductionmentioning
confidence: 99%